EFFECT OF MICROBIAL INOCULANTS AND INORGANIC FERTILIZERS ON GROWTH AND YIELD OF HYBRID CABBAGE (BRASSICA OLERACEA L. VAR.CAPITATA) - VIJAY KUMAR SINGH; SANGEETA SHREE; RAVI KUMAR; PARAMVEER SINGH; RAVI GOPAL SINGH (The Bioscan, 2015)
The present investigation was conducted to know the effect of different levels of inorganic fertilizers viz., F1=80:40:40 Kg NPK/ha, F2=120:60:60 Kg NPK/ha, F3=160:80:80 Kg NPK/ha, F4=200:100:100 Kg NPK/ha and F5=240:120:120 Kg NPK/ha and bio-fertilizers viz., M0-0, M1-Azotobacter, M2-Azospirillum, M3-VAM and M4-PSB. The experiment comprised of 25 different treatment combinations and replicated thrice. Results from the study indicated that combined application of NPK @ 200:100:100 Kg/ha along with seedling treatment with Azospirillum gave significantly higher plant height (30.40cm), plant spread (54.50cm), head diameter (24.32cm), head depth (21.71cm), head weight (1.878 Kg) and head yield (868.70 q/ha). However, days taken to head formation and head maturity, number of outer leaves/plant and number of inner leaves/head did not show significant interaction effects. Therefore, it may be concluded that combined application of NPK @ 200:100:100 kg/ha along with seedling treatment with Azospirillum was the most effective treatment combination for higher growth and yield in cabbage.